Zoning Patterns of Mangrove Forests in Lampung Timur Regency - Imron; Duryat; Irawan, Sandy Erggi; Tri Maryono; Rodiani (Journal of Sylva Indonesiana, 2024)
Mangrove forests form due to vegetative distribution along coastlines with varying growing conditions concerning substrate, freshwater intake, and oceanic currents. These disparities facilitate zoning and subsequent distinct growth patterns. The research objective was to identify the zoning structure of mangrove ecosystems in Lampung Timur Regency, Lampung Province, Indonesia. The degradation of mangrove forests in Lampung Timur Regency was thought to be caused by anthropogenic activities and inappropriate zoning patterns. Concerning data collection, the cluster sampling method was employed, which was selected based on the preliminary study's findings that the mangrove status in the study area exhibits a variety of substrates, freshwater supply, and strong ocean currents. There are five clusters on the study site, with each cluster containing sample plots measuring 10m x 10m. The sampling method employed a striped path starting from the outermost part of the mangrove ecosystem, with the number of plots in each cluster dependent on the thickness of the mangrove vegetation. A regional map and GIS applications were used for mangrove zonation mapping, and the factors influencing the zonation of mangrove ecosystems were analyzed descriptively. The research findings demonstrated that the mangrove ecosystem located in Lampung Timur comprises three distinct zones: the outer zone, the middle zone, and the terrestrial zone